Modulation of the vault protein-protein interaction for tuning of molecular release - Yu, Kang (2018)
Vaults are naturally occurring ovoid nanoparticles constructed from a protein shell that is composed of multiple copies of major vault protein (MVP). The vault-interacting domain of vault poly(ADP-ribose)-polymerase (INT) has been used as a shuttle to pack biomolecular cargo in the vault lumen. However, the interaction between INT and MVP is poorly understood. It is hypothesized that the release rate of biomolecular cargo from the vault lumen is related to the interaction between MVP and INT. To tune the release of molecular cargos from the vault nanoparticles, we determined the interactions between the isolated INT-interacting MVP domains (iMVP) and wild-type INT and compared them to two structurally modified INT: 15-amino acid deletion at the C terminus (INTΔC15) and histidine substituted at the interaction surface (INT/DSA/3 H) to impart a pH-sensitive response. The apparent affinity constants determined using surface plasmon resonance (SPR) biosensor technology are 262 ± 4 nM for iMVP/INT, 1800 ± 160 nM for iMVP/INTΔC15 at pH 7.4. The INT/DSA/3 H exhibits stronger affinity to iMVP (K Dapp = 24 nM) and dissociates at a slower rate than wild-type INT at pH 6.0.